PRINCIPALS COMPONENTS VARIABLES OF TARO WHITE CATTLE MORPHOMETRICS BASED ON BODY MEASUREMENT - Heryani, Luh Gde Surya; Susari, Ni Nyoman Werdi; Gunawan, I Wayan Nico Fajar (Buletin Veteriner Udayana, 2018)
The taro white cattle is a unique group cattle with a very small number of population and only can be found at Taro forest at Tegallalang.  The taro white cattle population was decreasing and already in critical condition. Breed characterization is a primary step in designing appropriate management and conservation programs.  To support the conservation effort, the objective of this study is to assess the phenotypic profiles of the taro white cattle based on the body measurement. Morphometric profiles identification of the taro white cattle was conducted on 24 adult taro white cattle, the measured variables were head length, head width, body height, chest depth, body length, chest width, chest circumference, and hip length. The result showed that the body length, body height, chest width, chest circumference, hip height, head length and head width mean was significantly different between males and females. In contrast, between the chest depth and the hip width of males and females, there was no significant difference. The principal component analysis (PCA) test showed that the first major components were long body size, height, and hip height, while the second major component was a chest depth. The obtained results can use as phenotypic profile of taro white cattle and are important for the future development of conservation and management strategies for taro white cattle breed in order to prevent the loss of biodiversity in Indonesia.